A Critical Review of Diet Supplementation - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
There has been a massive surge in the intake of dietary supplements in recent years, with millions of people taking the “magic pills” worldwide, either with the hope of achieving general well-being, treat specific disease, or retard the aging process. Supplementing the diet with multivitamins and minerals (MVMs) has revolutionized modern healthcare, with many “experts” claiming such drugs have a critical role to play in the prevention and treatment of many health conditions. Many are of the opinion that since dietary supplements are mere extracts from certain foods and herbs, so unlike drugs, have no significant side effects, are “all natural,” and are therefore “safe” for a non-medical prescription. The association of the deficiency of some MVMs, such as vitamins C, D, and Zinc, with the increased incidence and progression of COVID-19, has also strengthened the argument in favor of routine diet supplementation. The objectives of this article are to investigate the health and therapeutic claims attributed to some dietary supplements, their safety concerns, and their possible role in modern healthcare. A review of related online free-full articles written in the English language published from 2000 to 2021 was done. While the pharmacokinetics and pharmacodynamics of some dietary supplements are clearly understood and established, others are still shrouded in serious confusions and safety concerns, especially for long-term use. Until more evidence is available, routine intake of dietary supplements should be discouraged, except there are clear medical indications. Rather, all people should ensure they get their required nutrients from whole foods.